JURIDICAL ANALYSIS OF THE IMPLEMENTATION OF TICKET FINE SANCTIONS IN ELECTRONIC TRAFFIC LAW ENFORCEMENT (E-TLE) AGAINST TRAFFIC VIOLators ACCORDING TO THE LAW LAW NUMBER 22 OF 2009 CONCERNING TRAFFIC AND ROAD TRANSPORT (IN THE JURISDICTION REGIONAL POLICE OF NORTH SUMATRA) - Rosy, Deuis Rina (Inspiring Law Journal, 2024)
Electronic Trafficking Law Enforcement (ETLE) is an electronic system for monitoring traffic law enforcement which takes the form of ETLE Implementation itself, generally designed with the provisions of Law Number 22 of 2009 regarding Lailu Liintais and Aingkutain Jailain, including other enforcement agencies ETLE reaches the limit with this goal but still no success effective. Maikai dairii is necessary to research regarding the maisailaihain. This thesis is entitled